Bisphenol A at environmentally relevant doses induces cyclooxygenase-2 expression and promotes invasion of human mesenchymal stem cells derived from uterine myoma tissue - Kai-Hung Wang; An-Pei Kao; Chia-Cheng Chang; Ta-Chin Lin; Tsung-Cheng Kuo (Elsevier, 2013)
Objective: Uterine myoma is the most common benign reproductive tract tumor in women. Despite its high prevalence, the exact pathogenesis of these benign tumors remains unknown. Toward understanding the pathogenic mechanism of these tumors, we attempted to isolate human uterine myoma mesenchymal stem cells (hUM-MSCs), which may be the target cells for tumorigenesis. Furthermore, we tested the response of these hUM-MSCs to the environmental endocrine disruptor, bisphenol A (BPA), which may mimic the action of estrogen in hormone-sensitive organs such as the uterus. Materials and Methods: The hUM-MSC lines were clonally derived from uterine myoma tissue using the MSU-1 medium supplemented with N-acetyl-l-cysteine and l-ascorbic acid-2-phosphate. These hUM-MSCs were characterized by reverse transcription polymerase chain reaction (RT-PCR) analysis for the expression of mesenchymal stem cell (MSC) surface markers (e.g., CD90 and CD105) and the transcription factor Oct-4. The proliferation potential was measured by the cumulative population doubling level and the colony-forming efficiency. Results: Putative hUM-MSC lines expressed CD90, CD105, and the stem cell marker gene, Oct-4. The cells were capable of differentiating into adipocytes, osteoblasts, and chondrocytes. Bisphenol A treatment of these hUM-MSCs enhanced cell proliferation and colony-forming efficiency in a dose-responsive manner. At an environmentally relevant concentration (10−8 M), BPA moreover induced cyclooxygenase-2 (COX-2) gene expression and promoted cell migration and invasiveness. Conclusion: The hUM-MSC cell lines can be isolated from uterine myoma tissues. Bisphenol A could enhance cell proliferation and colony-forming efficiency, induce COX-2 gene expression, and promote migration and invasion of hUM-MSCs. The results imply that BPA has a detrimental effect on female health by promoting uterine tumorigenesis.